Utilization of Health Insurance for Outpatient in the Community: A Meta-Analysis - Nagaring, Sulaiman Putra; Murti, Bhisma; Tamtomo, Didik (Journal of Health Policy and Management, 2022)
Background: Health insurance is the answer to the uncertainty of the occurrence of illness and the need for health services. To ensure that the need for health services can be adequately financed, a person or small group of people transfers risk to another party called an insurer/insurer, or an insurance agency.Subjects and Method: This was a systematic review and meta-analysis conducted with PRISMA flow diagrams. Search articles through journal databases including: Google Scholar, MEDLINE/ PubMed, Science Direct and Spinger Link by selecting articles published in 2000-2021 The keywords used are “health care”AND “outpatient” OR “insurance” AND “private health insurance” AND “outpatient” OR “health insurance” AND “private health insurance” AND “utilization of public health care” AND “inpatient service” AND “outpatient service” AND “logistic regression aOR”. The inclusion criteria were full paper articles with retrospective study cohort research methods, the analysis used was multivariate with adjusted Odds Ratio (aOR), the intervention provided was health insurance, the research subjects were private health insurance users. Eligible articles were analyzed using the RevMan 5.3 application.Results: A meta-analysis of 9 articles showed that people with private health insurance were 1.98 times more likely to use outpatient services than those without health insurance, and the effect was statistically significant (aOR = 1.98; 95% CI = 1.39 to 2.81; p<0.001).Conclusion: The use of private health insurance has a statistically significant effect in increasing outpatient use.Keywords: health insurance, private health insurance, outpatient, meta analysis.Correspondence: Sulaiman Putra Nagaring. Masters Program in Public Health. Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: sulaimanputran@gmail.com Mobile: 085855533027Journal of Health Policy and Management, (2022), 07(02): 158-165https://doi.org/10.26911/thejhpm.2022.07.02.07